2021
DOI: 10.4236/ajmb.2021.113006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Possible Link of Intestinal Microbiota and Type 2 Diabetes Mellitus

Abstract: Introduction: This study assessed the role of gut bacteria in the development of type 2 Diabetes Mellitus. Methodology: Using bacteria cultural method, microbial species were isolated from feacal materials, identified and quantitated through application of genomic spectrophotometric systems with a quantitation of some marker biochemical parameters for Diabetes. Result: We observed a concentration of firmicutes, bacteriodetes, protecbacteria and bifidobacterium with Escherichia coli population predominating. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Throughout life, the gut microbiota acts as a sensory hub, responding to both intrinsic and extrinsic stimuli affecting host physiology within and outside the gut [14]. Disruption of a delicate balance among the gut microbes has been linked to the development of metabolic diseases particularly type 2 diabetes mellitus [5], obesity [15], and cardiovascular disorders [16]. Most of the earlier studies reported differences between the gut microbiome of diabetics, prediabetics, and healthy nondiabetic individuals [6,17], and very few examined the gut microbiome of treatmentnaive T2DM individuals [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, the gut microbiota acts as a sensory hub, responding to both intrinsic and extrinsic stimuli affecting host physiology within and outside the gut [14]. Disruption of a delicate balance among the gut microbes has been linked to the development of metabolic diseases particularly type 2 diabetes mellitus [5], obesity [15], and cardiovascular disorders [16]. Most of the earlier studies reported differences between the gut microbiome of diabetics, prediabetics, and healthy nondiabetic individuals [6,17], and very few examined the gut microbiome of treatmentnaive T2DM individuals [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, alterations in the gut-junction protein, endocannabinoid system, and intestinal alkaline phosphatase are caused by changes in microbiota-dependent bacteria. Some probiotics have been shown to reduce the onset of diabetes by acting as interleukin (IL), IFN, or even influencing anti-inflammatory IL-10 production, according to research [9]. Other research has found that high fructose-fed rats have lower levels of serum glucose, insulin, leptin, c-peptide, glycated hemoglobin, GLP, inflammatory IL-6, and TNF in adipose tissue, and PPAR-and Glut4 gene expression [10].…”
Section: Introductionmentioning
confidence: 99%